1976
DOI: 10.1017/s0043174500063025
|View full text |Cite
|
Sign up to set email alerts
|

The Light Requirement for Herbicidal Activity of Diphenyl Ethers

Abstract: Light after treatment was found to be required for the herbicidal activity of nitrofen (2,4-dichlorophenyl-p-nitrophenyl ether) and oxyfluorfen [2-chloro-1-(3-ethoxy-4-nitrophenoxy)-4-(trifluoromethyl)benzene] following postemergence applications of both herbicides to greenbean (Phaseolus vulgarisL. ‘Spartan Arrow’). The effect of photosynthate and/or light before treatment was investigated. A 24-hr dark period prior to postemergence treatment of the bean seedlings had no effect on herbicidal activity when lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 11 publications
3
23
0
Order By: Relevance
“…This may have accounted for the increased permeability of the yellow leaves to paraquat and oxyfluorfen. Fadayomi & Warren (1976), using fresh weight determinations at 3 days after treatment, showed that the yellow soybean mutant and the normal green plants were equally susceptible to oxyfluorfen. Matsunaka {1969a), working with several rice mutants in the light, showed that white mutants were resistant to a diphenylether (nitrofen), while yellow mutants were as susceptible as the normal green ones.…”
Section: Plant Pigments and Herbicidal Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…This may have accounted for the increased permeability of the yellow leaves to paraquat and oxyfluorfen. Fadayomi & Warren (1976), using fresh weight determinations at 3 days after treatment, showed that the yellow soybean mutant and the normal green plants were equally susceptible to oxyfluorfen. Matsunaka {1969a), working with several rice mutants in the light, showed that white mutants were resistant to a diphenylether (nitrofen), while yellow mutants were as susceptible as the normal green ones.…”
Section: Plant Pigments and Herbicidal Activitymentioning
confidence: 98%
“…In contrast Baur et al (1969) claimed that ultrastructural changes such as rapid disintegration ofthe plasmaiemma in mesophyll cells of paraquat-treated leaves of Prosopis juliflora were similar after incubation in either light or darkness. Fadayomi & Warren (1976) showed that light was required for activity of oxyfluorfen in beans. Matsunaka (!969a, 1969b) found that the ortho substituted dipheny!…”
Section: Light and Dark Studiesmentioning
confidence: 99%
“…Nitro-and chloroDPE molecules absorb a portion of the UV-A component. This is based in part on the fact that DPEs are inactive in plants lacking carotenoids due to mutation or chemical treatment (Fadayomi and Warren, 1976;Matsunaka, 1969). Photooxidation of /?-car in UV-A radiation in the absence of herbicide was greater than in visible light alone (Table III), corroborating the fact that carotenoids absorb UV-A radiation.…”
Section: Discussionmentioning
confidence: 78%
“…The presence of light and oxygen are the basic requirements to induce activity of DPhE herbicides such as oxyfluorfen and acifluorfen (Fadayomi and Warren 1976). It has been reported that DPhE herbicides generate oxygen radicals, which initiate a free radical chain reaction in the cell membrane (Orr and Hess 1982;Boger 1984).…”
Section: Introductionmentioning
confidence: 99%